Cryo-EM Structure of the Flagellar Motor Complex from Paenibacillus sp. TCA20 - Sakura Onoe; Tatsuro Nishikino; Miki Kinoshita; Norihiro Takekawa; Tohru Minamino; Katsumi Imada; Keiichi Namba; Jun-ichi Kishikawa; Takayuki Kato (Biomolecules)
The bacterial flagellum, a complex nanomachine composed of numerous proteins, is utilized by bacteria for swimming in various environments and plays a crucial role in their survival and infection. The flagellar motor is composed of a rotor and stator complexes, with each stator unit functioning as an ion channel that converts flow from outside of cell membrane into rotational motion. Paenibacillus sp. TCA20 was discovered in a hot spring, and a structural analysis was conducted on the stator complex using cryo-electron microscopy to elucidate its function. Two of the three structures (Classes 1 and 3) were found to have structural properties typical for other stator complexes. In contrast, in Class 2 structures, the pentamer ring of the A subunits forms a C-shape, with lauryl maltose neopentyl glycol (LMNG) bound to the periplasmic side of the interface between the A and B subunits. This interface is conserved in all stator complexes, suggesting that hydrophobic ligands and lipids can bind to this interface, a feature that could potentially be utilized in the development of novel antibiotics aimed at regulating cell motility and infection.